The Effects of Irrigation, Genotype and Additives on Tef Silage Making - Philip Wagali; Chris Sabastian; Yehoshua Saranga; Shiran Ben-Zeev; Sameer J. Mabjeesh (Animals, 2023)
Tef is known as a multi-harvest crop with high production capacity and outstanding fodder quality. Hence, our overall goal is to develop tef as a new multi-harvest summer crop that can maintain high-quality feed and contribute to both field crops and the livestock industry in Israel. In this study, we aimed to evaluate the ability to preserve tef as silage. Four tef genotypes grown under well-watered (100%) and water-limited (75%) irrigation regimes were harvested at grain filling stage and ensiled with either no additives (control, CTL), or with heterofermentative inoculum (HI), molasses (MOL), and both MOL + HI. Our results showed for the first time that tef could be ensiled, although water-soluble carbohydrates (WSC) were lower than those in corn, “the perfect ensiling crop”. Most of the tef silage qualitative parameters were better at water-limited irrigation. Additives HI or MOL or MOL + HI also improved silage parameters, e.g., lowered pH and ammonia nitrogen content, but increased in vitro dry matter digestibility, lactic acid and crude protein content, and lactic acid bacteria counts of tef silage. The current results imply increasing the diversity of local ruminant fodder crops, ensuring high-quality feed supply during the summer.